2017
DOI: 10.3389/fnins.2017.00237
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wealth Shocks on Loss Aversion: Behavior and Neural Correlates

Abstract: Kahneman and Tversky (1979) first demonstrated that when individuals decide whether or not to accept a gamble, potential losses receive more weight than possible gains in the decision. This phenomenon is referred to as loss aversion. We investigated how loss aversion in risky financial decisions is influenced by sudden changes to wealth, employing both behavioral and neurobiological measures. We implemented an fMRI experimental paradigm, based on that employed by Tom et al. (2007). There are two treatments, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
4
4
0
Order By: Relevance
“…Let us first consider how prospective gains and losses modulate brain activation. Consistent with previous research ( Tom et al., 2007 ; Canessa et al., 2013 ; Charpentier et al., 2016 ; Pammi et al., 2017 ), we observed partially overlapping sets of positive-value coding regions that showed activation that increases with the magnitude of prospective gains ( β gain, neutral > 0) or deactivations that become more negative with the magnitude of prospective losses ( β loss, neutral < 0) in the neutral-face condition. These regions include the bilateral striatum, ventral tegmental area, dorsal anterior cingulate cortex, anterior insula, paracingulate gyrus and rostral ACC/vmPFC, among others ( Figure 3A and Supplementary Table S1 for ROI-based and S2 for whole-brain results).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Let us first consider how prospective gains and losses modulate brain activation. Consistent with previous research ( Tom et al., 2007 ; Canessa et al., 2013 ; Charpentier et al., 2016 ; Pammi et al., 2017 ), we observed partially overlapping sets of positive-value coding regions that showed activation that increases with the magnitude of prospective gains ( β gain, neutral > 0) or deactivations that become more negative with the magnitude of prospective losses ( β loss, neutral < 0) in the neutral-face condition. These regions include the bilateral striatum, ventral tegmental area, dorsal anterior cingulate cortex, anterior insula, paracingulate gyrus and rostral ACC/vmPFC, among others ( Figure 3A and Supplementary Table S1 for ROI-based and S2 for whole-brain results).…”
Section: Resultssupporting
confidence: 91%
“…Notably, we also observed this effect in the amygdala. This is in contrast to the mixed results of some previous studies ( Tom et al., 2007 ; Canessa et al., 2013 ; Gelskov et al., 2015 ; Charpentier et al., 2016 ) but in line with a recent study that found ‘neural loss aversion’ in the amygdala, though it was unrelated to behavioral loss aversion in that study ( Pammi et al., 2017 ). We also found activations for prospective losses in the left amygdala and in the mOFC/vmPFC, consistent with previous observations ( Basten et al., 2010 ; Canessa et al., 2013 ; Sokol-Hessner et al., 2013 ; Häusler et al., 2016 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…By making a loss salient, NES may shift risk preferences in the loss domain. This is consistent with the results of Pammi et al (2017). Moreover, subjects facing losses in the lab are more likely to show present bias and hyperbolic discounting (Haushofer, Schunk, & Fehr, 2013), which is correlated with loss aversion (Dean & Ortoleva, 2019).…”
Section: Introductionsupporting
confidence: 85%